Modalidade epistémica e evidencialidade nos sermões católicos na língua portuguesa (Studia Iberystyczne, 2014)
EVIDENTIALITY AND EPISTEMIC MODALITY IN CATHOLIC SERMONS IN PORTUGUESEEpistemic modality indicates the degree of certainty or doubt speakers have for the proposition expressed by their utterance. Evidentiality, on the other hand, is the indication of evidence for a statement in question. Given the eminently persuasive character of homiletic discourse, it features a high degree of epistemicity and frequently makes use of evidential markers. The preacher emphasizes his high degree of certainty about the content of what he says and, in order to gain credibility, he supports his reasons citing the Bible or other sources deemed reliable. This paper aims to analyze the markers of epistemic modality and evidentiality in Catholic sermons in Portuguese. Moreover, it intends to define the limit between different kinds of evidence. In order to carry out this analysis, fifteen homilies pronounced in the Sanctuary of Our Lady of Fátima have been examined.